Juvenile survival increases with dispersal distance and varies across years: 15 years of evidence in a prairie perennial - Lea K. Richardson; Scott W. Nordstrom; Amy Waananen; Riley D. Thoen; Amy B. Dykstra; Gretel Kiefer; Drake E. Mullett; Erin G. Eichenberger; Ruth G. Shaw; Stuart Wagenius (Ecology, 2024)
Juvenile survival is critical to population persistence and evolutionary change. However, the survival of juvenile plants from emergence to reproductive maturity is rarely quantified. This is especially true for long‐lived perennials with extended pre‐reproductive periods. Furthermore, studies rarely have the replication necessary to account for variation among populations and cohorts. We estimated juvenile survival and its relationship to population size, density of conspecifics, distance to the maternal plant, age, year, and cohort for Echinacea angustifolia , a long‐lived herbaceous perennial. In 14 remnant prairie populations over seven sampling years, 2007–2013, we identified 886 seedlings. We then monitored these individuals annually until 2021 (8–15 years). Overall, juvenile mortality was very high; for almost all cohorts fewer than 10% of seedlings survived to age 8 or to year 2021. Only two of the seedlings reached reproductive maturity within the study period. Juvenile survival increased with distance from the maternal plant and varied more among the study years than it did by age or cohort. Juvenile survival did not vary with population size or local density of conspecific neighbors. Our results suggest that low juvenile survival could contribute to projected population declines.